[SbW9O33]-based polyoxometalate combined with a phase transfer catalyst: A highly effective catalyst system for selective oxidation of alcohols with H2O2, and spectroscopic investigation - Ingle, Rohit H.; Raj, N. K. Kala; Manikandan, Palanichamy (Journal of Molecular Catalysis A-Chemical, 2007)
Na-9[SbW9O33] in conjunction with a phase transfer catalyst, methyltricapryl ammonium chloride, is highly efficient for selective oxidation of variety of alcohols with aq. H2O2 to yield corresponding carbonyls. Most importantly the reactions are carried out in the absence of any organic solvents especially halogenated solvents. In case of allylic alcohols, the catalyst is highly selective for the alcohol oxidation reaction and least selective for epoxidation reaction in the presence of aq. H2O2. IR studies support the formation of W-peroxo intermediate species and also support the stability of the catalyst in the presence of phase transfer compound under the present experimental condition. The catalyst can be reused after careful decomposition of peroxide of the final reaction mixture. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Alcohol; Aq.H2O2; Nag[SbW9O33]; Oxidation; Phase transfer catalyst; Polyoxometalate; polyoxotungstate

Lacunary Keggin type polyoxotungstates in conjunction with a phase transfer catalyst: an effective catalyst system for epoxidation of alkenes with aqueous H2O2 - Ingle, Rohit H.; Raj, N. K. Kala (Journal of Molecular Catalysis A-Chemical, 2008)
Na-9[SbW9O33] in conjunction with a phase transfer catalyst (methyl tricapryl ammonium chloride) is a highly efficient catalytic system for the selective epoxidation of alkenes with aqueous H2O2 as the oxidant. Importantly, the reactions can be carried out in the absence of any organic solvents. The alkene epoxidation reactions with both, a transition metal ion substituted polyoxotungstate as well as a transition metal ion free polyoxotungstate precursor indicates that the tungstate group is the active center for the oxidation reaction. It was also observed that the transition metal ion does not play any significant role in the reaction. IR studies support the formation of tungsten-peroxo species and also show that the catalyst is stable in the presence of phase transfer catalyst when aqueous H2O2 is used as an oxidant. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: alkenes; Aqueous H2O2; epoxidation; Na-9[SbW9O33]; Phase transfer catalyst; polyoxometalates

Immobilization of phosphotungstic acid (PTA) on imidazole functionalized silica: evidence for the nature of PTA binding by solid state NMR and reaction studies - Sofia, L. T. Aany; Krishnan, Asha; Sankar, M.; Raj, N. K. Kala; Manikandan, Palanichamy; Rajamohanan, P. R.; Ajithkumar, Thalasseril G. (Journal of Physical Chemistry C, 2009)
Phosphotungstic acid (PTA) immobilized onto imidazole functionalized fumed silica and was used its an efficient catalyst for epoxidation of a variety of olefins using aqueous H(2)O(2) as all oxidant. Negligible leaching of PTA under the reaction conditions employed indicates a strong interaction between PTA and imidazole The immobilized catalysts Could be separated and reused after the catalytic cycle Evidence for the heterogenization of PTA oil the imidazole functionalized fumed silica has been inferred from different spectroscopic techniques like IR, UV-vis, and NMR. Importantly, the nature of binding of PTA oil the support has been studied in detail by solid state NMR spectroscopy using (15)N labeled imidazole Support. It is clear from the NMR Studies that the effective heterogenization of PTA is mainly due to imidazolium ion Formation oil the support by the acidic protons of PTA and the resultant ion pair